Clinical gap changes after porcelain firing cycles of zirconia fixed dentures - TÜRKER, ŞEBNEM BEGÜM (KOREAN ACAD PROSTHODONTICS, 2014)
PURPOSE. The aim of this study was to measure the changes on the marginal and internal adaptation of zirconia based anterior fixed partial dentures after the porcelain firing process. MATERIALS AND METHODS. A total of 34 anterior fixed partial dentures using LAVA CAD/CAM system (3M ESPE, Germany) were applied. Two silicone replicas were obtained: one is obtained before porcelain firing process (initial) and the other is obtained after porcelain firing process (final), followed by the examination under a binocular stereomicroscope. Kruskal Wallis and Wilcoxon Signed Ranks tests were used for the statistical analysis (P<.05). RESULTS. No statistically significant difference was found between initial and final marginal gap values (P>.05). At the internal gap measurements, final marginal area values (59.54 mu m) were significantly lower than the initial marginal area values (68.68 mu m)(P<.05). The highest and the lowest internal gap values were observed at the incisal/occlusal area and at the marginal area, respectively. In. addition, lower internal gap values were obtained for canines than for central incisors, lateral incisors and premolars at the incisal area (P<.05). CONCLUSION. The firing cycles did not affect the marginal gap of Lava CAD/CAM system, but it is controversial for the internal gap.
Keywords: Zirconia; Resin cement; Surface treatment; Marjinal gap; Internal gap; MARGINAL FIT; DENTAL PROSTHESES; INTERNAL GAPS; IN-CERAM; DISTORTION; CROWNS